2005
DOI: 10.2337/diabetes.54.9.2727
|View full text |Cite
|
Sign up to set email alerts
|

LEW.1WR1 Rats Develop Autoimmune Diabetes Spontaneously and in Response to Environmental Perturbation

Abstract: We describe a new rat model of autoimmune diabetes that arose in a major histocompatibility complex congenic LEW rat. Spontaneous diabetes in LEW.1WR1 rats (RT1 u/u/a ) occurs with a cumulative frequency of ϳ2% at a median age of 59 days. The disease is characterized by hyperglycemia, glycosuria, ketonuria, and polyuria. Both sexes are affected, and islets of acutely diabetic rats are devoid of ␤-cells, whereas ␣-and ␦-cell populations are spared. The peripheral lymphoid phenotype is normal, including the frac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
55
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 49 publications
3
55
0
Order By: Relevance
“…Infection of rats with Kilham rat virus (KRV) leads to T1D within 2-4 wk after viral inoculation in 50% of the infected rats (22). LEW1.WR1 rats have normal T lymphocyte levels and function (23), and the disease is characterized by a selective loss of islet b cells, glycosuria, ketonuria, and polyuria (23,24). We recently hypothesized that the innate immune system plays a key role in virus-induced T1D (25,26), and demonstrated that TLR-mediated innate immune activation synergizes with viral infection to promote disease induction (26).…”
mentioning
confidence: 99%
“…Infection of rats with Kilham rat virus (KRV) leads to T1D within 2-4 wk after viral inoculation in 50% of the infected rats (22). LEW1.WR1 rats have normal T lymphocyte levels and function (23), and the disease is characterized by a selective loss of islet b cells, glycosuria, ketonuria, and polyuria (23,24). We recently hypothesized that the innate immune system plays a key role in virus-induced T1D (25,26), and demonstrated that TLR-mediated innate immune activation synergizes with viral infection to promote disease induction (26).…”
mentioning
confidence: 99%
“…For example, upregulation of TLR3 and RLH pathways with Poly I:C induces diabetes in PVG, WAG, and WF rats [ 190,191], with PVG rats the most susceptible to disease induction [191]. Of note, breaking immunological tolerance in these animals requires repeated activation of the innate immune system over a period of two weeks and sometimes the use of relatively high doses of Poly I:C [190][191][192][193], probably due to the presence of low frequencies of beta cell-specific T cells [180]. The induction of diabetes by TLR3 upregulation is thought to be controlled by iddm4 [192], is restricted to strains expressing Class II u molecules and is not evident in rats expressing Class II a or Class II c [191], consistent with the critical role of Class II antigens in human diabetes [54,61].…”
Section: Fig (1) Model For Virus-and Tlr-induced Diabetes In the Bbmentioning
confidence: 98%
“…We have therefore used the biobreeding diabetes resistant (BBDR) and LEW1.WR1 rat models to delineate how infection with Kilham rat virus (KRV) leads to islet destruction. These animals have normal Tcell proportions and function [16]. Disease triggered by KRV is immune mediated, as diabetes can be prevented by a treatment with antibodies directed against the Tcell receptor, CD5, and CD8 [17,18], and the transfer of spleen cells from virus-infected rats to class II u compatible rats adoptively transfers insulitis and diabetes [17,18].…”
Section: The Lew1wr1 Rat Model Of Virus-induced Type 1 Diabetesmentioning
confidence: 99%
“…Disease triggered by KRV is immune mediated, as diabetes can be prevented by a treatment with antibodies directed against the Tcell receptor, CD5, and CD8 [17,18], and the transfer of spleen cells from virus-infected rats to class II u compatible rats adoptively transfers insulitis and diabetes [17,18]. Infection with KRV leads to insulitis and diabetes characterized by selective loss of islet beta cells (Figure 1), glycosuria, ketonuria, and polyuria in the LEW1.WR1 and BBDR rats, but not other rat strains [16][17][18][19][20]. Susceptibility to virus-induced diabetes is dependent on the presence of class I A u and class II B/D u [17,18].…”
Section: The Lew1wr1 Rat Model Of Virus-induced Type 1 Diabetesmentioning
confidence: 99%